Nutritional status in under five children and their associated risk factors in an urban slum of Mumbai - Chowdhury, Aishani; Gupta, Animesh (International Journal of Research in Medical Sciences, 2021)
Background: Young children living in urban slums are at high risk for acute malnutrition and stunting. Many factors contribute towards it including living conditions, gender, delivery method, or access to nutrition. Malnutrition at a young age can cause morbidity and mortality, and impact further development and educational outcomes of children, and cause lifelong impairment. The aim of this study was to assess the nutritional status of young children in an urban slum in Mumbai and the factors affecting the health of children. Methods: A community based cross sectional study was conducted in the slum community of Dharavi, Mumbai. Data was collected using pre-designed and pre-tested proforma by interview method. Results: The prevalence of wasting (W/H) was found in 48.9% of the population in this study, of which 25.0% had severe acute malnutrition (SAM) and 23.9% had moderate acute malnutrition (MAM). Stunting was found in 39.7% of the population, of which 29.5% were moderately stunted and 10.2% were severely stunted. Wasting was found to be highly correlated with the age of the child and the age of the mother, whereas Stunting was found to be highly correlated with the child, the age of the mother, and complementary feeding. Conclusions: Poor nutritional status of children in the urban slums in Mumbai needs to be addressed by improving education and awareness amid parents and access to Anganwadi, Balwadi, and nutritional supplements.